International trade and exchange rates - Jong Woo Kang; Suzette Dagli (Journal of Applied Economics, 2018)
This paper analyzes the link between international trade and exchange rate levels in the context of the global financial crisis (GFC) and the rise of global and regional value chains (GVCs). Using bilateral data for 72 economies over the 2001-2015 period, we find a positive relationship between the real exchange rate and export volume pre-GFC; but this relationship mostly disappears post-GFC. We also examine the impact of deepening GVCs on trade and on the exchange rate-trade link channel. The analysis confirms that increased participation in GVCs lowers the impact of the exchange rate on exports, and could be a contributing factor to weakening links between exchange rates and trade. Lastly, other structural factors, such as import composition and stock of short-term external debt of exporters and importers, seem to have a significant impact on trade performance but less impact on the exchange rate-trade link channel post-GFC.
Keywords: 330; global value chains; gravity model; real exchange rate; Trade volume